The geoeconomic impacts of China's Belt and Road Initiative on Iran: benefits and challenges - Mohammadreza Mohammadi; Mohammad Sadegh Sohrabi; Saeed Rabiei (Discover Global Society)
Abstract The Belt and Road Initiative (BRI), proposed by China, is recognized as one of the largest and most challenging global infrastructure development projects. China's purely economic approach has encouraged many countries along the BRI route to participate in this project. The BRI has significant impacts on the countries along its route, including Iran. Due to its geographical location, Iran is a historical bridge on the historic Silk Road, connecting the East and the West, and a route to Europe. It is also of great cultural, economic, and strategic importance, and can join this Chinese program in the fields of science, technology, transportation, energy, and investment. This initiative has major effects on Iran's geoeconomics and plays a vital role in its economic and social development. This article provides a comprehensive examination of the impacts of China's Belt and Road Initiative on Iran's geoeconomic, analyzing the opportunities, challenges, and the economic and strategic implications of this initiative for Iran. It seeks to answer the question of Iran's position in the BRI and what the consequences of this initiative will be for Iran's geoeconomy. The research findings indicate that the successful implementation of the BRI can enhance economic cooperation in the region, revive Iran's geoeconomic position, and enable Iran to play a more active role in non-Western collaborations, providing Tehran with an opportunity to evade Western sanctions. However, the article also examines potential challenges, such as increased economic dependency on China and negative environmental impacts. It offers recommendations for optimizing the opportunities presented by the BRI and mitigating its challenges. The results of this research show that despite Iran's central position in the BRI and its strategic geographic location, it has not fully benefited from the advantages of this project.